Pemberdayaan Remaja Putri melalui Edukasi Interaktif Menyusui Berbasis Sekolah untuk Dukungan Menyusui Berkelanjutan - Idarto, Areta; Indawati, Maria Natalia; Agung Shinta Kamaya, I Dewa Ayu; Kencanawati, Nathania Dwi; Lenggu, Hendrik Hanok; Sabilillah, Alya Ilma; Rizkha, Yulia Nurlaela; Khairunnisa, Nisrina (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
One strategic approach to supporting maternal, child, and environmental health is enhancing breastfeeding literacy among adolescents. However, education efforts are often limited to pregnant and breastfeeding mothers. During World Breastfeeding Week (WBW) 2025 at SMA Muhammadiyah 2 Surabaya, an intervention was conducted to raise awareness among female adolescents about the importance of breastfeeding. More than 100 students participated in the “Tree of Hope” activity, which included presentations, discussions, and breastfeeding simulations. Evaluation results showed a 46% increase in understanding and strengthened commitment among participants to support breastfeeding practices. Teachers and students also received educational leaflets and a DIGIbook as learning resources. Aligned with the WBW 2025 theme, “Prioritize Breastfeeding: Create Sustainable Support Systems,” this program reinforced the role of adolescents as part of a long-term breastfeeding support ecosystem and fostered early preventive values and social empathy through a multimodal approach combining education, practice, and reflective participation.